Physiology of the Autonomic Nervous System - Ashirqulova Sevinch; Sayfulloyeva Sevinch; Sultanbayeva Ruxsora (Scholars Digest Publishing, 2023)
In this article, we will talk about the physiology of the autonomic nervous system. Autonomic, i.e., vegetative nervous system (Latin: vegetatio - growth, development, movement) is a part of the nervous system of humans and vertebrates; the fibers of the autonomic nervous system spread to the smooth muscles of all internal organs and control their activity without the will of a person (autonomously). But the autonomic nervous system operates under the control of the cortex of the large hemispheres of the brain, like animal nerves (spreading to skeletal muscles). This term was introduced to science for the first time by the French doctor M. Bisha (1801) and scientifically justified its difference from the activity of the somatic nervous system. The English physiologist J. Langley (1903) called the autonomic nervous system the "autonomic nervous system" because the activity of the autonomic nervous system is not controlled by consciousness, therefore it is also called the "autonomic" or involuntary nervous system.
Keywords: Vegetative nervous system, autonomic, sympathetic, parasympathetic, nerve, innervation, efferent, afferent, somatic, metabolism.